African Women : Early History to the 21st Century - Sheldon, Kathleen E., 1952- (Book collections on Project MUSE., 2017)
African women's history is a topic as vast as the continent itself, embracing an array of societies in over fifty countries with different geographies, social customs, religions, and historical situations. In African Women: Early History to the 21st Century, Kathleen Sheldon masterfully delivers a comprehensive study of this expansive story from before the time of records to the present day. She provides rich background on descent systems and the roles of women in matrilineal and patrilineal systems. Sheldon's work profiles elite women, as well as those in leadership roles, traders and market women, religious women, slave women, women in resistance movements, and women in politics and development. The rich case studies and biographies in this thorough survey establish a grand narrative about women's roles in the history of Africa.